2015
DOI: 10.1186/s10194-015-0553-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic loci for migraine susceptibility in the she people of China

Abstract: Background: The purpose of this study was to investigate the association of the genotype and allele frequencies of the polymorphisms rs4379368, rs10504861, rs10915437, rs12134493 and rs13208321 in She people of China with migraine headache susceptibility. The five alleles were previously identified as being associated with migraine in a Western population, but it was not known if this association would hold in a She population. rs4379368 is in the succinic HMG coenzyme A transferase (C7orf10) gene; rs10504861 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…Our findings differ from those of our previous study that examined the association of these same five SNPs in a She population 9. In contrast to the current study, that previous study found that the rs4379368 SNP did not conform with Hardy-Weinberg equilibrium in the migraine group and that the T allele was more common than the C allele in the She population, possibly indicating the presence of positive genetic selection for the T allele in the She population for migraine.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings differ from those of our previous study that examined the association of these same five SNPs in a She population 9. In contrast to the current study, that previous study found that the rs4379368 SNP did not conform with Hardy-Weinberg equilibrium in the migraine group and that the T allele was more common than the C allele in the She population, possibly indicating the presence of positive genetic selection for the T allele in the She population for migraine.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not assess the relationships of the SNPs evaluated in this study with these migraine-associated characteristics. Also, our previous analysis of a She population identified differences in specific genotypes between sexes 9. In the present study the sex ratio differed between the control (28% males and 72% females) and migraine (19.9% males and 80.1% females) groups ( p =0.057).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In our previous epidemiological study on migraines in the She population, the prevalence of migraines was as high as 10.53%, which is significantly higher than that in China overall (4.32%) [6,19]. Based on the five newly identified polymorphic loci from the abovementioned meta-analysis [17], we investigated the genotype distribution and allele frequency of those five polymorphic loci in the She population and Han Chinese to explore their correlation with migraines [20,21]. Our results showed that the SNPs rs4379368 (in c7orf10) and rs13208321 (in FHL5) were potential genetic markers for migraines in the She population [20].…”
mentioning
confidence: 99%